Review of Rethinking Japan’s Modernity by M. William Steele. Cambridge, Mass and London, 2025. 352 pages - Matsui, Nobuyuki (Silva Iaponicarum, 2026)
Review of Rethinking Japan’s Modernity by M. William Steele. Cambridge, Mass and London, 2025. 352 page.